Statistics on Partitions Arising from Seaweed Algebras - Coll Jr., Vincent E.; Mayers, Andrew W.; Mayers, Nicholas W. (The Electronic Journal of Combinatorics, 2020)
Using the index theory of seaweed algebras, we explore various new partition statistics. We find relations to some well-known families of partitions as well as a surprising periodicity result.